2022
DOI: 10.1007/s10639-022-11259-2
|View full text |Cite
|
Sign up to set email alerts
|

Predicting students’ performance in English and Mathematics using data mining techniques

Abstract: This study attempts to predict secondary school students' performance in English and Mathematics subjects using data mining (DM) techniques. It aims to provide insights into predictors of students' performance in English and Mathematics, characteristics of students with different levels of performance, the most effective DM technique for students' performance prediction, and the relationship between these two subjects. The study employed the archival data of students who were 16 years old in 2019 and sat for t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 72 publications
0
2
0
Order By: Relevance
“…The study emphasized the importance of previous academic success, demography, and psychological characteristics in predicting performance. The study also demonstrated that a student's previous Mathematics performance can predict their MCE English performance concluding that the two disciplines were interrelated [13].…”
Section: Related Workmentioning
confidence: 80%
See 1 more Smart Citation
“…The study emphasized the importance of previous academic success, demography, and psychological characteristics in predicting performance. The study also demonstrated that a student's previous Mathematics performance can predict their MCE English performance concluding that the two disciplines were interrelated [13].…”
Section: Related Workmentioning
confidence: 80%
“…Author year Method Accuracy [5] 2019 DANN 93 [6] 2020 DM 88.3 [7] 2021 ANN 0.82 [8] 2022 RF, XGBOOST, KNN, SVM 78 [9] 2022 RF, SVM, KNN, LR, NB 86.4 [10] 2023 ANN-LSTM 71.35 [11] 2023 DT 76.19 [12] 2023 DEEP LSTM 84.57 [13] 2023 DT, NB, SVM, NN 87.1 -204 213 [14] 2023…”
Section: Table 2: a Comparison Results With Related Workmentioning
confidence: 99%
“…Their data included 18 attributes in four dimensions: basic information, interests, classroom behavior, and extracurricular behavior, and had diverse data types. Muhammad Hazique Bin Roslan et al [4] predicted English and mathematics scores of 16-year-old Malaysian students using their past academic performance, demographics, and psychological information. They also explored the main factors that affect students' English and mathematics scores and the relationship between them.…”
Section: Related Workmentioning
confidence: 99%
“…The authors proposed that performance can be predicted by classroom activities, midterm scores and tests that can be held quarterly in a year [6]. The authors revealed that students' previous academic records played an important role in performance prediction while demographic and behavioral variables have less impact [7]. The authors also analyzed the current academic grades, attendance and assignment scores of 44 students but the accuracy of the prediction model was not so high [8].…”
Section: Introductionmentioning
confidence: 99%